Economics and ideologies of Slovenian literary mediation - Dović, Marijan (Primerjalna književnost, 2012)
This paper addresses the economics and ideologies that influenced Slovenian literary mediation in four very dissimilar historical periods of Slovenian book production and circulation: the Habsburg Monarchy (1779-1918), the interwar period (Royal Yugoslavia, 1918-1945), the communist period (Federal Yugoslavia, 1945-1991), and the democratic period (the Republic of Slovenia, from 1991). The analysis considers three groups of factors (or constraints) that condition the production and circulation of books (and ideas) in general: economic factors, political (ideological) factors, and networking factors. As a small system, Slovenian literature turns out to be special in many respects and only partly governed by market logic.
Keywords: družba; society; Slovene literature; slovenska književnost; zgodovina knjige; literarno posredništvo; založništvo; knjižni trg; ideologija